Hepatomegaly and short stature in a 14-year-old with type 1 diabetes mellitus: case report. (20th November 2020) - Fox, Miriam T; Tamaroff, Jaclyn; Percy, Andrew G; Baker, Stephanie; Altshuler, Courtney; Baluyot, Mariju; Stewart, Rosalyn W
Abstract: Background: Mauriac syndrome is a rare consequence of poorly controlled insulin-dependent diabetes, characterized by hepatomegaly, growth failure, delayed onset of puberty, and cushingoid features. Case reports of patients with Mauriac syndrome are found infrequently in the literature given historic improvements in diabetes management due to readily available insulin therapy. Methods: We describe a case of a 14-year-old girl who presented with acute onset abdominal pain, distention, and orthopnea. Results: She had a history of poorly controlled insulin-dependent diabetes as well as short stature. Abdominal imaging revealed impressive hepatomegaly. Laboratory testing showed markedly elevated triglycerides and cholesterol. Mauriac syndrome was suspected and diagnosed by liver biopsy, which demonstrated significant glycogenic hepatopathy. Conclusions: This case provides an illustrative example of Mauriac syndrome in a child who did not experience delayed onset of puberty and continued to have regular menses unlike what has been previously described. Furthermore, this case highlights the important consideration for significant dyslipidemia in patients with Mauriac syndrome and discusses the challenges of controlling insulin-dependent diabetes in the adolescent population.